Risk assessment of hepatocellular carcinoma development by magnetic resonance elastography in chronic hepatitis C patients who achieved sustained virological responses by direct‐acting antivirals. Issue 7 (3rd May 2019) - Tamaki, Nobuharu; Higuchi, Mayu; Kurosaki, Masayuki; Kirino, Sakura; Osawa, Leona; Watakabe, Keiya; Wang, Wan; Okada, Mao; Shimizu, Takao; Takaura, Kenta; Takada, Hitomi; Kaneko, Shun; et al.
Abstract: Prediction of hepatocellular carcinoma (HCC) development after sustained virological response (SVR) is clinically important, and the usefulness of noninvasive markers for prediction HCC have been reported. The aim of this study was to compare the prediction accuracy for HCC development by noninvasive markers. A total of 346 patients with chronic hepatitis C without history of HCC who achieved SVR through direct‐acting antivirals were included. Magnetic resonance elastography (MRE) and serum fibrosis markers were measured 12 weeks after the end of treatment, and the subsequent HCC development was examined. The mean observation period was 26.4 ± 7.9 months, and 24 patients developed HCC. Area under the receiver operating characteristic curve of liver stiffness by MRE, Wisteria floribunda agglutinin‐positive mac‐2 binding protein and FIB‐4 for predicting HCC within 3 years was 0.743, 0.697 and 0.647, respectively. The 1/2/3‐year rates of HCC development in patients with liver stiffness ≥3.75 KPa were 6.6%, 11.9% and 14.5%, whereas they were 1.4%, 2.5% and 2.5% in patients with liver stiffness <3.75 KPa ( P  < 0.001). Multivariate analysis revealed that liver stiffness ≥3.75 was an independent predictive factor for HCC development (hazard ratio, 3.51; 95% confidence interval, 1.24‐9.99). In subgroup analysis, there were 132 patients who were <73 years old and had liver stiffness <3.75 KPa, and no HCC development was observed in these patients. Diagnostic accuracy for predicting HCC development was higher in MRE than serum fibrosis markers and measurement of liver stiffness by MRE could identify patients with high and low risk of HCC development after SVR.